PENGARUH KUALITAS LAYANAN INTERNET BANKING SECARA KESELURUHAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Bank BNI Pekalongan) - Siti Nurhayati; Wenti Ayu Sunarjo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Abstract  The aims of this research is to analize the dimensions of internet banking, there have 3 dimensions : (1) online customer service quality, (2) online information system quality, and (3) banking service product quality,  and  their  influence  to  customer’s  satisfaction.  The  analyze  done  by  intervening  regression model with SPSS, and than examine both partial and simultaneous hypothesis. The sample amount 152 customers of BNI Pekalongan that using the internet banking service. The  procedures of analysis are :  a.  testing the instrument with validity and reliability, b. testing the classic assumption with normality, multicolinearity,and heteroscedasticity, c. intervening regression analysis with 2 models (substructure) regressions, d. testing the partial and simultan hypothesis The result of substructure 1 regression, show that on partial test, 3 independent variables above has the positive  and  significance  influence  to  overall  internet  banking  quality  service  at  the  level  of significance 95 % ( or at α 5 % ). On the simultaneous test also has the significance influence result. The test hypothesis of substructure 2  regression, showthat overall internet banking quality service has the significance influence. By those result, the management of BNI Pekalongan must optimalized the quality of internet banking service  that  can  increasing  the  customer’s  satisfaction,  because  it  was  make  the  positive  effect  of corporate image by the word of mouth informations. KEYWORDS : customer service; information system internet banking